Die ermordeten Kinder vom Spiegelgrund : Gedenkdokumentation für die Opfer der NS-Kindereuthanasie in Wien - Häupl, Waltraud 1935- (Böhlau, 2006)
A register of names of 788 children who died or were euthanized in Spiegelgrund. Includes biographical and medical information for each child.